KARAKTERANATOMI GALUR-GALUR HARAPAN KEDELAI (Glycine max L. Merill) TAHAN Cowpea Mild Mottle Virus (CpMMV) - Wijaya, Irwan; Zubaidah, Siti; Kuswantoro, Heru (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
Soybean Â is a staple commodities agricultural in Indonesia, but the production of soybean in Indonesia is still low due to the attacks of disease caused by infection of CpMMV. This research was conducted to study anatomical characteristics of the 10 soybean Â linesto CpMMV and two superior varieties.The research was conducted atJambegede Research Station, Indonesian Legume and Tuber Crops Research Institute, Malang andlaboratory of genetics, State University of Malang Â to observe the anatomy of leaf include the length, width, and number of stomata and the length and number of trikoma.The test was analyzed using one-way ANOVA. Results of the analysis showed significance > Î± (0.05) on each character, this indicates there is no difference in the character of both stomata and trikoma on 10 soybeanslines to CpMMVand two varieties superior.Kata kunci: Anatomi, kedelai, CpMMV